DAMPAK PERANG DAGANG TERHADAP NERACA PERDAGANGAN AMERIKA SERIKAT-CHINA - Meyland Wambrauw; Djoice N Menufandu (DAS Institute, 2022)
This paper aims to discuss the US-China trade war and its impact on the trade balance of the two countries and the global economy. The two countries’ trade war occurred in 2018 when the US imposed tariffs on imports to China. This article adopts qualitative descriptive research. Mercantilism theory and the concept of trade wars were also used to analyze the topic. This study found that the triggers for the trade war by Donald Trump against China were influenced by three factors: 1) a trade deficit experienced by the US; 2) the allegations of manipulating the dollar made by China, making the Yuan the main currency; 3) the allegations of US intellectual rights theft by China. This trade war also impacted the trade balance of the two countries, where China experienced a significant surplus while the United States experienced a deficit. Nonetheless, the United States still ranks first as a country with the world's highest Gross Domestic Product (PBD). The US-China trade war has also weakened global economic growth. This cannot be avoided because the US and China are economic superpowers that play a pivotal role in world trade, so actions taken in the context of a trade war will undoubtedly have an impact on other countries or regions